Childhood vitiligo: A hospital-based study on 200 patients in Northeast India - N A Bishurul Hafi; Nandakishore Singh Thokchom; Shyamsunder Ch Singh; Romita Bachaspatimayum (Wolters Kluwer Medknow Publications, 2019)
Background: Vitiligo is a depigmenting disorder which can be psychologically devastating. Childhood-onset vitiligo has different epidemiological and clinical characteristics as compared to adults. Aims and Objectives: The aim was to study the clinico-epidemiological and hematologic investigation profiles of childhood vitiligo. Materials and Methods: First 200 pediatric patients younger than 18 years, with vitiligo who attended the dermatology outpatient department of a tertiary center in Northeast India, between September 2015 and August 2017 were included in the study. A detailed history and examination along with autoimmune diseases and laboratory parameters were recorded. Results: Among the 200 patients, 62% were girls. The mean age was 10.3 ± 4.9 years. The mean age at onset was 9.1 ± 4.9 years (ranging 2 months-17 years), with duration of disease varying from 1 month to 8 years with mean duration of 1.39 ± 1.63 years. Most common pattern of vitiligo was vulgaris (39.5%) followed by focal (25%), segmental (15.5%) genital (10%), acral and lateral lip (8%), and acrofacial (4%). Family history of vitiligo was seen in 12% of patients. In 96% patients, only <5% of body surface area was affected. Nearly 8.5% had Koebnerization while 9% showed leukotrichia. Thyroid-stimulating hormone and antithyroid peroxidase abnormalities were seen in 4.5% and 1% patients, respectively. Low Vitamin D level was seen in 21.5%. Conclusion: Any depigmented lesion in children should be evaluated and followed up properly to rule out vitiligo. Dermatologists and pediatricians should understand the characteristics of childhood vitiligo properly since it behave differently from adult-onset disease.